2017
DOI: 10.1038/ncomms15915
|View full text |Cite
|
Sign up to set email alerts
|

Munc13-1 and Munc18-1 together prevent NSF-dependent de-priming of synaptic vesicles

Abstract: Synaptic transmission requires a stable pool of release-ready (primed) vesicles. Here we show that two molecules involved in SNARE-complex assembly, Munc13-1 and Munc18-1, together stabilize release-ready vesicles by preventing de-priming. Replacing neuronal Munc18-1 by a non-neuronal isoform Munc18-2 (Munc18-1/2SWAP) supports activity-dependent priming, but primed vesicles fall back into a non-releasable state (de-prime) within seconds. Munc13-1 deficiency produces a similar defect. Inhibitors of N-ethylmalei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 60 publications
2
102
0
Order By: Relevance
“…There is indeed evidence for binding of the SNARE four-helix bundle to Munc18-1 85,86,88 (see above) and to the Munc13-1 MUN domain. 104,105 Such binding might prevent disassembly of trans SNARE complexes by NSF-aSNAP and thus stabilize the primed state of readily releasable vesicles, as suggested by a recent study, 106 and could also mediate a direct involvement of Munc18-1 and/or Munc13-1 in membrane fusion as proposed in the models of Figure 1(G,H), but these models need further testing.…”
Section: Rizomentioning
confidence: 86%
“…There is indeed evidence for binding of the SNARE four-helix bundle to Munc18-1 85,86,88 (see above) and to the Munc13-1 MUN domain. 104,105 Such binding might prevent disassembly of trans SNARE complexes by NSF-aSNAP and thus stabilize the primed state of readily releasable vesicles, as suggested by a recent study, 106 and could also mediate a direct involvement of Munc18-1 and/or Munc13-1 in membrane fusion as proposed in the models of Figure 1(G,H), but these models need further testing.…”
Section: Rizomentioning
confidence: 86%
“…A second recent study highlighting the dynamic nature of the primed SV state (He et al, 2017) demonstrated ''de-priming'', i.e., a progressive loss of the primed SV state in the absence of the SNARE-regulating proteins Munc13-1 and Munc18-1. At rest, only a very small primed SV pool can be generated when Munc13-1 is deleted so that only the low endogenous Munc13-2-levels are remaining, or else, when Munc18-1 is replaced by Munc18-2.…”
mentioning
confidence: 99%
“…It was demonstrated that Munc13-1 catalyzes the transition of the Munc18-1/syntaxin-1 complex to the SNARE complex in the presence of SNAP-25 and synaptobrevin-2 [12,13]. Supporting such a scenario, increasing evidence revealed that Munc18-1 and Munc13-1 cooperate to ensure proper SNARE complex assembly [14], and stabilize primed synaptic vesicles (SV) in a manner resistant to NSF/a-SNAP [15,16]. These results illustrate a Munc18-Munc13 route to SNARE complex formation and suggest that the Munc18-1/syntaxin-1 complex may constitute a welldefined starting point amenable to exquisite regulation of exocytosis.…”
mentioning
confidence: 99%